INFORMATION NEEDS OF DIGESTIVE TRACT SURGERY PATIENTS BEFORE AND AFTER THE SURGERY: AN EXPLORATORY STUDY OF WESTERN LITHUANIA - Gedrime, Lina; Istomina-Fatkulina, Natalja; Brasaite, Indre; Salanterä, Sanna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The aim of this study was to describe the information needs of patients undergoing gastrointestinal surgery in Western Lithuania. Methods. This data were collected from patients of three Klaipeda city hospitals performing digestive tract surgeries in January – March 2015. The interview responses (n = 86) were analyzed inductively with thematic content analysis. Results. The interview revealed lack of information about disease, treatment and nursing care. The participants expressed fear and worries about their forthcoming surgery, anesthesia, pain, the ways of pain management, possible complications and their prevention as well as the future concerning their disease in general. Conclusions. The results show that the participants had not got enough information about treatment, nursing, anesthesia, rehabilitation, wound care or about post-surgery period. Instead they felt fear and anxiety. The participants were not included into treatment and nursing processes. According to the participants’ responses, the information needs were different before and after the surgery. Lack of information prevents patients from acting self-dependently in their care. Practice implications. Patient oriented approach to patient education and innovative ways of information delivery are needed in Lithuanian nursing care of patient’s having a gastrointestinal surgery.